POTENSI PANGAN FUNGSIONAL DAN PERANNYA DALAM MENINGKATKAN KESEHATAN MANUSIA YANG SEMAKIN RENTAN—MINI REVIEW - Abbas Abbas (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2020)
This work was aimed to review not only variations and defenition of functional food as well as its positive impact on health but also diseases which correspond with poor diet and its correlation to certain health status, consumers’ attitude and perception on functional food and potential of food from farm-based become functional food. There are 14 groups of bioactive as ingridient of food which have strong correlation toward status and sort of helath for instance, prebiotics and probiotics. As an effort to avoid the occurence of some diseases due to low nutrient diet, community development in terms of advocation and education play pivotal role on the impotance of functional food consumption. Yet, it is need support from local government as nearest authority to community and other stakeholders. Involving all stakelholders would be maximizing functional food production and it could be maintained its sustainability.